Hydro-mechanical analysis of fractured media using discontinuous deformation analysis - Choo, Ling Qian (2017)
It is well-established that pore pressure built up in discontinuities has a profound effect on the mechanical behaviors of the jointed rock masses. The discontinuous deformation analysis (DDA) is a discontinuum theory which can account for the interactions between pore pressure and rock mechanics. It is also a numerical method or computer program commonly applied to hydro-geomechanical modeling. Research and development of DDA hydro-mechanical model has been thriving over the last two decades. The main objective of this research study is to further contribute to those efforts. Specifically, the following works have been conducted to achieve this objective: (i) a seepage analysis extension is proposed to the DDA method for the modeling of seepage flow within jointed rock masses; (ii) to improve the computational efficiency of the extension in simulating quasi-static hydro-mechanical problems, a new solution scheme featuring a constant hydraulic aperture is introduced; (iii) a stochastic flow modeling extension is proposed to the DDA method for the simulation of heterogeneous hydraulic conductivity and aperture fields; (iv) a hydraulic crack initiation-propagation extension complete with a coupled hydro-mechanical analysis algorithm is introduced to the hybrid DDA-FEM model for the simulation of hydraulic fracturing problems. To investigate the reliability, efficiency and limitation of the proposed DDA extensions, a series of numerical examples are presented and discussed. The capability of the new DDA extensions in modeling realistic engineering problems are also verified through meaningful case studies.